CUTANEOUS LUPUS ERYTHEMATOSUS WITH AUTOANTIBODIES COLOCALIZING WITH GLIAL FIBRILLARY ACIDIC PROTEIN - Abreu-Velez Ana Maria; Smith J. Graham Jr; Howard Michael S. (Our Dermatology Online, 2011)
Background: Discoid lupus erythematosus (DLE) is a chronic, inflammatory skin disorder, presenting with scarring lesions predominating on sun exposed areas of the face and scalp. Case Report: A 43-year-old African American female was evaluated for possible DLE. Methods: Skin biopsies for hematoxylin and eosin (H&E) examination, as well as for direct immunofluorescence (DIF) analysis were performed. Results: H&E staining demonstrated classic features of cutaneous lupus erythematosus, with the pertinent presence of perineural lymphohistiocitic infiltrates, especially those associated with skin appendices. DIF revealed strong deposits of immunoglobulins IgG, IgM, fibrinogen and Complement/C3, present in a shaggy, linear pattern at or near the basement membrane zone (BMZ) of selected eccrine and sebaceous glands, and around some blood vessels. The BMZ positivity in these structures consistently colocalized with positive staining in multiple, punctate areas for glial fibrillary acidic protein (GFAP), including within cytoid bodies. Conclusions:. The observed colocalization of the patient's autoantibodies in cutaneous lupus with GFAP may have pathophysiologic relevance. Specifically, our data could be consistent with previously described DLE patients with or without overt central nervous system manifestations, or could represent an epiphenomenon. Additional, larger studies are needed to satisfactorily address this possibility.